Synthesis and Characterization Of C-Hexyl Calix[4]Resorcinarena from Resorcinol-Heptanal Condensation - Desi Suci Handayani; Zainal Arifin Almaqqomul Amin; Triana Kusumaningsih; Abu Masykur (UNIVERSITAS SEBELAS MARET (UNS), 2014)
Synthesis of C-hexyl calix[4]resorcinarene through condensation reaction between resorcinol and heptanal with HCl catalyst has been investigated. Synthesis conducted by the ratio of resorcinol: heptanal (1:1) using reflux for 6 hours in ethanol. Structural analysis of the product was done by FTIR and 1 H-NMR spectroscopy, while the characterization was done by determining melting point. The product was golden brown powder with a yield 99.43% and melting point more than 300 °C. Structural analysis with FTIR and 1 HNMR known vibration and signals characteristic of calix[4]resorcinarena group, the vibrations of the CH bridge. Vibration of CH bridge appearance at wave number 1445 cm-1 and 1456 cm-1, while signal of CH bridge appearance at chemical shifts from 4.17 to 4.21 ppm.